Sistema computacional para simulação e análise de redes com elevada presença de geração distribuída fotovoltaica - Tonini, Luiz Guilherme Riva (2023)
Seeking forms of sustainable energy close to consumption centers, the use of distributed generation was established, especially photovoltaic, which uses a system based on inverters that can possibly improve energy quality. This inverter-based system is represented by diferent models and operating modes. To assess the impact that a high presence of this equipment causes on the electrical system, it is necessary to obtain the voltage profile and fault information, which are obtained by the respective power flow and short-circuit calculations. The purpose of this thesis is to implement a computational system that allows the simulation of feeder networks in this condition of high integration of distributed generation. For this, a methodology will be presented that considers the generator model as a current controlled by voltage source following operating mode curves, as interpreted in the IEEE 1547-2020 standard. The system will use the IEEE 13, 34 and 123-node feeders as a database, with one generator on each load per phase. The quantities obtained will be validated against a phasor model from the MATLAB/Simulink platform. The results showed an average error of 1.94%, 2.39% and 3,11% and a gain in processing time of 1,209.43%, 2,185.24% and 1.095,40%, for the 13, 34 and 123 nodes, in the power flow, respectively. The error and the gain were obtained in relation to a tool whose simulation occurs in the time domain. From the results obtained, it is suggested the application of the platform in larger and more complex systems and analysis of the impact of distributed generation during the short circuit. Another use of the proposed methodology is in the evaluation of the behavior of the intermittency, where it will be applied to the daily curves of solar generation and power consumption, which demonstrated that: at times of low generation and high consumption, depending on the installed power and the network topology, it is necessary the installation of voltage regulators to avoid undervoltage and the generation and consumption curve have a more significant influence on phases with the highest installed active power, with fault current peaks (about 3 pu), where the generators must be disconnected from the network depending on the modes of operation, occurring in lower power phases during peak generation and in higher power phases in a combination of non-generation and higher consumption (≤ 70%).